Pemberdayaan Masyarakat Melalui Pengolahan Cabai Sundari Menjadi Abon Cabe Sundari Untuk Peningkatan Ekonomi Masyarakat - Nafilatur Rohmah; Imam Kukuh Prasetya (LPPM IAI TABAH, 2022)
The price of an abundant chili harvest is often not comparable to the cheap selling price of chilies. Therefore, the farmers suffer losses. Sundari chilies have advantages more then the others. But it has the similar selling price. Therefore, it is necessary to make efforts to increase the selling price of chilies to improve the economic of Lembor's community. The empowerment through processing Sundari chili into sundari chili floss is expected to be a stimulus for the community to be more creative and innovative in processing agricultural products. This community service is carried out using the PAR method with 9 PAR tools. The results of this community service are: 1. Participants have skills in processing Sundari chili into shredded sundari chili; 2. Participants get skill of attractive product packaging.They will also know the procedures for processing industrial licence from the Lamongan district cooperative office; 3. Participant also can know the skill for marketing techniques via online and offline. Then, they also can share their experiences from micro-entrepreneurs to attract participant motivation.